PENGARUH VALUE FOR MONEY TERHADAP KUALITAS PELAYANAN PUBLIK DENGAN TRANSPARANSI SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA WAJIB PAJAK DI KANTOR SAMSAT KOTA PALANGKA RAYA) - Gregorius Sugeng Tri Nugroho; Yohanes Joni Pambelum; Ferry Christian (Balance: Media Informasi Akuntansi dan Keuangan, 2021)
This study aims to provide an empirical explanation of the effect of value for money on public service quality with transparency as a moderating variable. The research method used in this research is descriptive statistical analysis, data instrument testing (validity and reliability tests), hypothesis testing, and determination coefficient test. The total population of this study consisted of 138.939 active tax payer that registered at Palangka Raya City SAMSAT office using slovin method which settled by researcher gained 100 people as sample that represent population. The type of data used is primary data. The collected data were analyzed using IBM SPSS Statistics version 25. The results showed that the first hypothesis of value for money has an effect on public service quality accepted. The second hypothesis of transparency as a moderating variable strengthen the effect of value for money on public service quality unaccepted